Resettlement schemes for agricultural development : the Leeward Islands of the Caribbean community - Liverpool, N J D (IDRC OttawaCA, 1987)
The first phase of this research project aims to determine whether land settlement schemes are conducive to better agricultural development in Antigua and Montserrat. Discusses socio-political background of land tenure policies in the Leeward Islands and focuses on land settlement legislation and government policy towards farmers. Outlines methodology of the project and personal characteristics of the farmers. Highlights marketing, irrigation, labour, and other problems faced by farmers. Analyses relationship of farmers to land. Makes recommendations on land settlement and on agricultural development.